On The Solution of Existence of Nonlinear Integral-and Integrodifferential Equations - Noora L. Husein (College of Education for Pure Sciences, 2018)
In this paper we study the existence and uniqueness for mixed Volterra - Fredholm integral and integrodifferential equations By using the extensions of Banach's contraction principle in complete cone metric space